2007
DOI: 10.1038/sj.onc.1210604
|View full text |Cite
|
Sign up to set email alerts
|

Distinct GCN5/PCAF-containing complexes function as co-activators and are involved in transcription factor and global histone acetylation

Abstract: Transcription in eukaryotes is a tightly regulated, multistep process. Gene-specific transcriptional activators, several different co-activators and general transcription factors are necessary to access specific loci to allow precise initiation of RNA polymerase II transcription. As the dense chromatin folding of the genome does not allow the access of these sites by the huge multiprotein transcription machinery, remodelling is required to loosen up the chromatin structure for successful transcription initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
314
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(331 citation statements)
references
References 167 publications
(255 reference statements)
7
314
1
6
Order By: Relevance
“…Like HAT1, Gcn5, PCAF and many other HATs Lee and Workman, 2007;Nagy and Tora, 2007;Parthun, 2007), MOZ and MORF are catalytic components of protein complexes. They were recently found to be stoichiometric subunits of ING5 (inhibitor of growth 5) complexes (Doyon et al, 2006).…”
Section: Moz and Morf As Catalytic Subunits Of Quartet Complexesmentioning
confidence: 99%
“…Like HAT1, Gcn5, PCAF and many other HATs Lee and Workman, 2007;Nagy and Tora, 2007;Parthun, 2007), MOZ and MORF are catalytic components of protein complexes. They were recently found to be stoichiometric subunits of ING5 (inhibitor of growth 5) complexes (Doyon et al, 2006).…”
Section: Moz and Morf As Catalytic Subunits Of Quartet Complexesmentioning
confidence: 99%
“…H3 tail peptide covering amino acids 5-20 was incubated with radioactive acetyl-coenzyme A and the indicated protein or protein complex preparation. Reactions were carried out in quadruplicate in the presence (H3 amino acids [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] or absence of the H3 tail peptide, and acetylation was measured in cpm. Error bars indicate S.D.…”
Section: Figure 2 Acetylation Activity Of the Gcn5 Enzyme Depended Omentioning
confidence: 99%
“…Later it was shown that this enzyme is homologous to the yeast Gcn5 protein, already known to be required for transcriptional activation (7)(8)(9)(10). Gcn5 is evolutionary highly conserved from yeast to human (5,11). Initial in vitro studies using microsequencing of labeled yeast histone H3 or H4 peptides and recombinant Gcn5 indicated that the enzyme displays a non-random specificity, mainly acetylating histone H3 at Lys-14 and to some extent H4 at Lys-8 position (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of other TAFs in cancer and/or metastasis has already been brought into light (7,46), however, this is the first report linking TAF4b itself with the regulation of tumor cell migration. Herewith, we provide evidence that TAF4b is a suppressor of cell migration regulating, in concert with c-Jun, the expression of genes playing a pivotal role in EMT.…”
Section: Taf4b Is Linked To Cell Migration Mechanisms and Emtmentioning
confidence: 99%